2013
DOI: 10.1111/vop.12029
|View full text |Cite
|
Sign up to set email alerts
|

Intra and inter‐user reliability of central corneal thickness measurements obtained in healthy feline eyes using a portable spectral‐domain optical coherence tomography device

Abstract: The Optovue® iVue SD-OCT device is capable of obtaining CCT measurements with excellent intra and interoperator reliability in healthy feline eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 24 publications
2
34
1
Order By: Relevance
“…Fourier‐domain OCT (FD‐OCT) has also been used for diagnosing and monitoring other anterior segment conditions such as conjunctivochalasis and been used for assessing the tear meniscus of humans . In veterinary ophthalmology, OCT has been primarily used in canine retinal and glaucoma research and there are currently limited data available on OCT values of the canine anterior segment . Studies have found SD‐OCT to be a reliable tool for measuring CCT in dogs …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourier‐domain OCT (FD‐OCT) has also been used for diagnosing and monitoring other anterior segment conditions such as conjunctivochalasis and been used for assessing the tear meniscus of humans . In veterinary ophthalmology, OCT has been primarily used in canine retinal and glaucoma research and there are currently limited data available on OCT values of the canine anterior segment . Studies have found SD‐OCT to be a reliable tool for measuring CCT in dogs …”
Section: Introductionmentioning
confidence: 99%
“…In veterinary ophthalmology, OCT has been primarily used in canine retinal and glaucoma research and there are currently limited data available on OCT values of the canine anterior segment . Studies have found SD‐OCT to be a reliable tool for measuring CCT in dogs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the veterinary ophthalmic literature, the use of OCT was first reported in 2007 in a study evaluating retinal structure in the cat and in 2008 to describe the retinopathy of the Coton de Tulear dogs . Recently, several studies have used OCT to characterize the normal cornea, iridocorneal angle, and retina in several species, as well as corneal abnormalities in dogs and cats . In the majority of these studies, the animals were under general anesthesia or deep sedation to avoid eye movement during imaging …”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the conventional “upright-sitting” counterpart (RTVue, Optovue Inc., Fremont, CA, USA) of iVUE SDOCT is a well-known device with excellent repeatability and reproducibility in measuring CCT [1620], though measurements cannot be used interchangeably with those made by USP [1820]. Another recent study in feline eyes has also shown that the iVUE SDOCT is capable of obtaining CCT measurements with excellent intra- and interoperator reliability [27]. Further studies will be needed to establish the accuracy of SDOCT pachymetric measurements with clinicopathological evaluations of the cornea and to study the safety and efficacy of performing CXL in corneas of the thicknesses as measured by SDOCT.…”
Section: Discussionmentioning
confidence: 99%